Asymptomatic bacteriuria in pregnancy and its effect on maternal and fetal outcomes - Gupta, Gaurika; Gautam, Roli (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Asymptomatic bacteriuria is the most common infection encountered in pregnancy and can lead to multiple complications both in mother like acute pyelonephritis, sepsis and in the fetus like LBW, preterm labour, PROM, if left untreated. The present study was done to determine the current prevalence of ASB and its maternal and perinatal outcome. Methods: A prospective cohort study was conducted at a tertiary centre on 150 antenatal females. Urine culture and sensitivity was conducted for each participant and the fetomaternal outcome between affected and unaffected women were compared and p value <0.05 was considered significant. Results: 27 females had ASB making the prevalence of 18% out of which 12 (44.4%) cultures yielded Klebsiella and 15 (55.5%) samples were sensitive to nitrofurantoin. There was no significant increase in antenatal complications, mode of delivery, post natal complications, neonatal outcomes. Conclusions: There is no significant risk associated with ASB, therefore the next question opens regarding the need for treatment.